CuICuII and AgIp-isocyanobenzoates as novel 1D semiconducting coordination oligomers. Issue 35 (27th August 2020) - Reguera, Leslie; Cano, Arely; Rodríguez-Hernández, Joelis; Rivera, Daniel G.; Van der Eycken, Erik V.; Ramírez-Rosales, Daniel; Reguera, Edilso
Abstract : Novel Cu I Cu II and Ag I 1D coordination oligomers based on the μ-η 1 :η 1 - p -isocyanobenzoate ligand form microfibers with interesting semiconducting properties. Abstract : Two novel semiconducting coordination oligomers with 1D chain structures, namely [H0.07 CuI0.65CuII0.14(μ- p -CNC6 H4 CO2 )·0.9H2 O] n and [Ag(μ- p -CNC6 H4 CO2 )] n, were obtained and characterized by XRD powder patterns, and XPS, EPR, UV-vis-NIR, IR and Raman spectroscopy. According to XRD analysis, Cu I Cu II –ICNBA is an amorphous solid, while Ag I –ICNBA crystalizes with a monoclinic unit cell in the C 2/ c space group ( Z = 4). The composition and further information of Cu I Cu II –ICNBA were obtained from the spectroscopic data. In correspondence with the quantification of terminal groups from high-resolution XPS spectra, Cu I Cu II –ICNBA and Ag I –ICNBA are composed of an average of 9 and 7 monomer units, respectively, resulting in 1D-oligomers. The spectroscopic evidence indicates that Cu I Cu II –ICNBA is better described as a non-stoichiometric coordination oligomer (where non-integer ratios of metal ions can be accommodated), while Ag I –ICNBA is stoichiometric. In both materials, each metal center is linked by two μ-η 1 :η 1 - p -isocyanobenzoate ligands forming microfibers of around 120 nm (Cu I Cu II -material) and 310 nm (Ag I -material) in average diameters with optical band gaps of 2.60 eV and 2.17 eV, respectively.